Cumulative Ambient Light Exposure Affects Outpatient Transcutaneous Bilirubinometer Readings - Emily Zhang; Tzong-Jin Wu; Mark L. Hudak; Ke Yan; Ru-Jeng Teng (Children)
Background: We recently reported that the transcutaneous bilirubinometer (TCB) tends to underestimate the severity of neonatal jaundice (NJ). We hypothesize that the cumulative ambient light exposure contributes to the discrepancy. Objectives: This study aimed to identify factors that affect the TCB underestimation. Methods: We analyzed prospectively collected data over a twenty-month period at a level III medical facility. Neonates at risk for NJ who couldn’t secure an appointment with the primary practitioner were followed by the nursery team. Neonates who had phototherapy or forehead bruises were excluded. Concurrently collected total serum bilirubin (TSB) was determined by the diazo method. The primary endpoint was the discrepancy between TCB and the corresponding TSB (TCB-TSB). A mixed-effects model was used to assess the correlation between (TCB-TSB) and potential contributors, including visit age (in hours), gestational age (GA), sex, TSB, season, birth weight, and race. Results: There were 795 visits for 559 neonates, including 341 males, 179 white, 235 black, 103 Hispanic, 41 Asian, and one unrecorded race. The TSB ranged between 1.8 and 33.9 mg/dL. The (TCB-TSB) ranged between −20.0 and 6.4 mg/dL. The median GA and birth weight were 38.7 weeks and 3214.5 g. The visits occurred between 48 and 381 h of age. 133, 148, 132, and 146 visits were in Spring, Summer, Autumn, and Winter, respectively. Fifty-four neonates (9.7%) were admitted for management. 500 sternum TCB readings were also collected from 350 neonates together with the corresponding forehead TCBs. We found that the forehead (TCB-TSB) was significantly less in winter than in spring and summer (p = 0.0014 and 0.0003, respectively). There was a negative correlation between forehead (TCB-TSB) and visit age in hours (p = 0.0006). After adjusting for visit age and season, the (TCB-TSB) is significantly correlated with TSB (p < 0.0001). Similar findings were also seen in the sternum (TCB-TSB) except for the season (p = 0.0808). Conclusions: Cumulative ambient light exposure and the severity of NJ may contribute to (TCB-TSB).